Characteristics, outcome and treatments with cranial pachymeningitis: A multicenter French retrospective study of 60 patients. Issue 30 (July 2018) - Mekinian, Arsene; Maisonobe, Lucas; Boukari, Latifatou; Melenotte, Cléa; Terrier, Benjamin; Ayrignac, Xavier; Schleinitz, Nicolas; Sène, Damien; Hamidou, Mohamed; Konaté, Amadou; Guilpain, Philippe; Abisror, Noémie; et al.
Abstract : Abstract: The aim of this study was to determine the characteristics, treatment, and outcome according to each etiology of pachymeningitis. We conducted a retrospective multicenter French nationwide study between 2000 and 2016 to describe the characteristics, outcome, and treatment of pachymeningitis. We included 60 patients (median age 55.5 years; interquartile range [IQR] 30–80, female/male ratio 0.43). Neurologic signs were present in 59 patients (98%) and consisted of headache in 43 (72%), cranial nerve palsy in 33 (55%), confusion in 10 (17%), seizures in 7 (12%), and focal neurologic signs in 9 (15%). Fever and weight loss were present in 8 (13%) and 13 cases (22%), respectively. Cerebral venous thrombosis was present in 8 cases (13%). Analysis of cerebrospinal fluid showed moderate hyperproteinorachia (median 0.68 g/L; IQR 0.46–3.2) with or without pleiocytosis. Diagnosis included idiopathic pachymeningitis (n = 18; 30%); granulomatosis with polyangiitis (n = 13; 17%); Erdheim-Chester disease (n = 10; 17%); IgG4-related disease and tuberculosis (n = 3; 5% each); Rosai-Dofman disease, microscopic polyangiitis, and sarcoidosis (n = 2, 3% each); cryptococcal meningitis, Lyme disease, ear-nose-throat infection, postlumbar puncture, low spinal-fluid pressure syndrome, and lymphoma (n = 1 each). We found no difference in demographics and neurologic presentation among idiopathic pachymeningitis, Erdheim-Chester disease, and granulomatosis with polyangiitis. In contrast, frequencies were lower with idiopathic pachymeningitis than Erdheim-Chester disease for general signs (6% and 40%, respectively, P  = .041) and complete neurologic response (0% vs 39%, P  = .045). The detection of extraneurologic signs and routine screening are needed to classify the pachymeningitis origin. Prospective studies are warranted to determine the best treatment in each case.